Hippocampal volume is related to olfactory impairment in Parkinson's disease. Issue 6 (6th August 2021) - Roh, Haewon; Kang, June; Koh, Seong‐Beom; Kim, Jong Hyun
Abstract: Background and Purpose: Recent evidence has suggested that hyposmia in patients with Parkinson's disease (PD) may be due to impaired central processing. Furthermore, the hippocampus has been regarded as a critical structure linking olfactory impairment and cognitive impairment in PD patients. This study aimed to identify significant structural alterations of the hippocampus in PD patients with hyposmia, and to determine whether these structural changes are significantly associated with olfactory impairment severity. Methods: Eighteen idiopathic PD patients with hyposmia and 18 age‐ and sex‐matched PD patients without hyposmia were enrolled. Hippocampal volume and its subfields were measured using FreeSurfer software and compared between hyposmic and normosmic PD patients. We also compared hippocampal substructures' volumes and correlated the hippocampal volumes with hyposmia severity. Results: PD patients with hyposmia had significantly smaller hippocampal volumes. Among the three components of the hippocampus, the hippocampal body showed a markedly lower volume, which correlated significantly with the cross‐cultural smell identification test score that represents olfactory function status. Hippocampal subfield analysis showed that substructures (subiculum, molecular layer) that constitute the hippocampal body showed the most significant volume difference. Conclusions: We suggest that atrophy of the bilateral hippocampus implies underlying problems in the central olfaction process in PD patients. In particular, the hippocampus might not only play a critical role in olfaction but could also be important for elucidating possible mechanisms of broad nonmotor symptoms in PD patients.